2022
DOI: 10.1111/resp.14224
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of virtual bronchoscopic navigation with fused fluoroscopy and vessel mapping for access of pulmonary lesions

Abstract: Background and objective Virtual bronchoscopic navigation (VBN) with fused fluoroscopy and vessel mapping provides a point of entry (POE) for puncturing airway wall to biopsy lesions. The study was designed to evaluate the safety and efficacy of this technology to diagnose peripheral pulmonary lesions. Methods It was a prospective, single‐arm, multicentre study. Patients underwent lesions biopsy with the Archimedes® VBN System via a POE using one of the two techniques: (1) bronchoscopic transparenchymal nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Sun et al demonstrated the efficacy and safety profile of using fused fluoroscopy and vessel mapping to aid with virtual bronchoscopic navigation and pulmonary lesion sampling. The avoidance of virtually mapped blood vessels during transparenchymal nodule sampling may have contributed to their low rate of airway bleeding [ 20 ]. This may be clinically relevant, especially when sampling pulmonary lesions that are central and adjacent to larger pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al demonstrated the efficacy and safety profile of using fused fluoroscopy and vessel mapping to aid with virtual bronchoscopic navigation and pulmonary lesion sampling. The avoidance of virtually mapped blood vessels during transparenchymal nodule sampling may have contributed to their low rate of airway bleeding [ 20 ]. This may be clinically relevant, especially when sampling pulmonary lesions that are central and adjacent to larger pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the C‐arm + X‐ray also indirectly guides the correct puncture direction of the FlexNeedle needle, reducing the risk of the operation and improving the success rate of the operation. Based on CT scan, Archimedes magnetic navigation imaging software virtual left main bronchus images before and after patency 20 and further evaluated the changes of left main bronchus after silicone stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…And on top of updates in pre-existing technologies such as EMN, several novel navigation bronchoscopy technologies have been introduced with the potential to further improve diagnostic yield. New kids on the block that aim to help diagnose peripheral pulmonary nodules now include specialized navigation instruments (21), robotics (22)(23)(24)(25)(26), cone beam CT (CBCT) (27)(28)(29)(30), mobile 3D C-arm imaging (31,32) and hybrid methods that combine modalities for navigation guidance and confirmation (33,34).…”
Section: Technological Innovationsmentioning
confidence: 99%